Civil engineering practice in the twenty-first century knowledge and skills for design and management - Grigg, Neil S.; Criswell, Marvin E.; Fontane, Darrell G.; Siller, Thomas J. (ASCE Press, 2001)
"In addition to designing, building, and managing the constructed environment, civil engineers have important environmental management responsibilities. lb succeed in these tasks, civil engineers must possess both management skills and technical tools. The Accreditation Board for Engineering and Technology, studies of the civil engineering work force, and engineering practitioners confirm the need for such skills and tools. The 12 chapters that comprise this book will assist students in developing those skills and prepare practitioners for the civil engineering challenges of the twenty-first century. Chapters discuss such topics as civil engineering heritage and future, consequences of civil engineering, work and careers in civil engineering, engineering design and the infrastructure life cycle, management, critical thinking, communications, government, finance and economics, law, and professional practice and ethics."